IMPOLITENESS IN THE E-NEWS SOCIAL MEDIA COMMENT SECTION: A DESCRIPTIVE STUDY - Adib Jasni Kharisma (Universitas Pendidikan Ganesha, 2023)
The purpose of this study was to examine impoliteness in the E-News social media comment section. Internet users frequently did not aware they were using an unfriendly phrase. This study employs a qualitative approach to explore impoliteness methods based on Culpeper's theory. It investigates the impoliteness techniques indicated by internet users in the E-News Instagram account's comment area. The information was gleaned from CNN's political comment section. In the E-News social media comment section, five impoliteness strategies were discovered: bald on record impoliteness, positive impoliteness, negative impoliteness, sarcasm or mock politeness, and withhold politeness. The highest strategy implemented by internet users in the E-News social media comment section was positive impoliteness. Meanwhile, the following causes contribute to the use of impoliteness in the E-News social media comment section: disagreement, anger, frustration, disappointment and lack of trust, seeking change/betterment, emotions, relief/happiness, and dishonesty.